Review: The role of HMGB1 in spinal cord injury - Mo, Yizhang; Chen, Kebing (Frontiers in Immunology, 2023)
High mobility group box 1 (HMGB1) has dual functions as a nonhistone nucleoprotein and an extracellular inflammatory cytokine. In the resting state, HMGB1 is mainly located in the nucleus and regulates key nuclear activities. After spinal cord injury, HMGB1 is rapidly expressed by neurons, microglia and ependymal cells, and it is either actively or passively released into the extracellular matrix and blood circulation; furthermore, it also participates in the pathophysiological process of spinal cord injury. HMGB1 can regulate the activation of M1 microglia, exacerbate the inflammatory response, and regulate the expression of inflammatory factors through Rage and TLR2/4, resulting in neuronal death. However, some studies have shown that HMGB1 is beneficial for the survival, regeneration and differentiation of neurons and that it promotes the recovery of motor function. This article reviews the specific timing of secretion and translocation, the release mechanism and the role of HMGB1 in spinal cord injury. Furthermore, the role and mechanism of HMGB1 in spinal cord injury and, the challenges that still need to be addressed are identified, and this work will provide a basis for future studies.